Polypharmacy and anticholinergic burden scales in older adults: a cross-sectional study among psychiatric outpatients in a tertiary care hospital - Manjunath Bidarolli; Biswadeep Das; Vikram Singh Rawat; Sachin Manocha; Hannah Theresa Sony; Akash Agnihotri; Mahima Gupta; Franklin Agera (BMC Geriatrics)
Abstract Introduction Mental disorders are prevalent among older adults, often leading to the use of multiple medications, many with anticholinergic properties. Polypharmacy, common in this population, is a major contributor to anticholinergic burden, which is linked to cognitive and physical decline. This study investigates the relationship between polypharmacy and anticholinergic burden across seven anticholinergic burden scales in elderly patients attending the psychiatric outpatient. Methods Study was conducted at a psychiatry outpatient clinic at All India Institute of Medical Sciences, Rishikesh, India, from December 2021 to March 2023. Elderly patients (aged ≥ 60 years) who were on at least one psychotropic medication and had a primary working diagnosis of psychiatric illness were included. All psychotropic medications, including antidepressants, antipsychotics, mood stabilizers, and hypnotics, were evaluated. Anticholinergic burden scales were calculated by the respective tools. Univariate analysis was adopted to determine the factors that may affect polypharmacy. Results Study included 1165 elderly patients aged ≥ 60 years. The prevalence of polypharmacy was 20.43% (n = 238). Clonazepam (n = 364, 17.28%), escitalopram (n = 197, 9.35%), metformin (n = 165, 7.83%), sertraline (n = 141, 6.69%), mirtazapine (n = 129, 6.12%), and lorazepam (n = 110, 5.22%) were among the most frequently prescribed anticholinergic drugs. Univariate analysis demonstrated that all anticholinergic risk assessment scales were closely correlated with polypharmacy, with the strongest association observed for the Anticholinergic Load Scale (ALS) (Odds Ratio = 4.3; p < 0.001). Polypharmacy was also positively associated with adverse drug reactions (Odds Ratio = 1.81; 95% Confidence Interval = 1.27–2.56). Conclusion The anticholinergic burden in this cohort of elderly psychiatry patients was high, with 95.1% (n = 1108) experiencing a significant burden. Adverse drug events and anticholinergic burden scales were positively associated with polypharmacy, with a stronger correlation between polypharmacy and ALS scores than with other anticholinergic burden scales in older adults.